The use of project activities in the interactive education of undergraduate students studying physical education - Usacheva I.N.; Moiseeva L.V.; Novichkova N.M.; Grineva E.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study aims to theoretically confirm the importance of using project activities in a group format. This interactive approach is considered as a means of improving the quality of mastering natural science disciplines and developing the necessary competencies in future bachelors studying at the Institute of Physical Education, Sports and Life Safety. The emphasis is on the use of a competency‑based approach in education. Methods and structure of the study. An analysis of information sources on the research problem was conducted. Results and conclusions. Practical experience shows that to work effectively, a physical education teacher needs not only specialized knowledge, but also developed general cultural competencies. This gives him the opportunity to fully participate in the socialization of secondary school students, which presupposes a high degree of responsibility based on respect for the individual, understanding of needs and awareness of life goals. The use of a project‑based approach in the educational process helps to increase the effectiveness of modern teaching methods aimed at the high‑quality acquisition of the necessary professional skills. The key element of project work is interactive interaction in small groups, where the educational team becomes a close‑knit team united by common tasks and goals. In the course of joint activities, common values are formed and experience of interpersonal communication is acquired, which will be useful in future professional activities.